Assessment of the carbon sequestration potential in temperate grasslands of the Hainich Biodiversity Exploratory in dependence of future climate and management scenarios - Matthias Filipiak; Katrin Kuka (Discover Environment)
Abstract Soil organic carbon (SOC) sequestration is crucial for mitigating climate change and regulating soil functions. Temperate permanent grasslands thereby have a high potential to sequester SOC due to an extended growing season under future climate conditions. Using the CANDY model, this study evaluates the SOC sequestration potential of 50 grassland sites in the Hainich Biodiversity Exploratory by subjecting each site to six contrasting management options under 18 future climate datasets spanning a period from 2008 to 2100. Simulations indicate that increasing management intensity through higher livestock units (up to 4 LU ha−1) or high mowing frequency (up to 5 cuts per year) leads to substantial SOC gains, especially on less intensively used sites. However, beyond a certain intensity threshold, the benefits of intensification diminish. This reduction in effectiveness may be due to factors such as increased water demand, soil compaction and disruption of nutrient cycles. Moderate grazing intensification (2–3 LU ha−1) and moderate mowing intensification (up to 3–4 cuts per year) are recommended in the Hainich region to maximise SOC sequestration while minimising negative impacts and maintaining resilience to future climate change. Soil compaction was identified as a central threat to future SOC sequestration, particularly under high management intensity, whereby soils with clay contents > 15% were most susceptible. This study highlights the need for balanced management strategies to enhance SOC sequestration in temperate grasslands. The CANDY model’s findings align with broader literature, underscoring the importance of integrated, sustainable land management to achieve long-term climate mitigation and soil health goals.